Development of the novel antiplatelet agent ADTM, originating from traditional Chinese medicine: a chemical proteomic analysis and in-vivo assessment of efficacy in an animal model. (October 2016) - Cui, Guozhen; Ho, Angela Wa; Lee, Simon Ming Yuen; Wang, Yuqiang; Hoi, Maggie Pui Man
Abstract: Background: An ageing population and lifestyle changes have led to increased cardiovascular disease-related morbidity and mortality in China, where an estimated 230 million people have cardiovascular disease. Long-term antiplatelet therapy with aspirin and clopidogrel are used for treatment and post-stenting primary prevention of acute coronary syndrome, but the risk of bleeding complications is high. This study aimed to identify the target of the newly developed antiplatelet agent ADTM, originating from traditional Chinese herbs. We also investigated the antiplatelet and cardioprotective effects of ADTM. Methods: We developed ADTM by conjugating danshensu and tetramethylpyrazine, which are active compounds in the herbs danshen ( Salvia miltiorrhizae ) and chuanxiong ( Ligustium wallichii Franch ), respectively. To identify the target of ADTM, we incubated its biotinylated analogue with rat blood platelet lysates, then used chemical proteomics to precipitate protein complexes. We compared the antiplatelet effect of ADTM with clopidogrel in a rat model in vivo by administrating ADTM (5–20 mg/kg) and clopidogrel (18 mg/kg) intravenously daily for 5 days, and inducing platelet aggregation by adenosine diphosphate. We also assessed the inhibitory effects of ADTM and clopidogrel on ferric chloride (FeCl3 )-induced venous thrombus formation. We further assessed the cardioprotective effects of ADTM in a canine coronary artery occlusion-reperfusion model. The left anterior descending coronary artery was occluded for 20 min followed by reperfusion in five beagles (weighing about 12 kg). 15 min after occlusion, ADTM (6mg/kg) or nitroglycerin (45 μg) was administered for 3 min continuously. Findings: Results of chemical proteomics showed that ADTM targets ERp57. The inhibitory effects of ADTM on platelet aggregation were similar to clopidogrel in the rat model (mean 40% [SD 11] for ADTM [p=0·018 vs control] and 38% [9] for clopidogrel [p=0·0073 vs control; p=0·78 vs ADTM). Similarly, the inhibitory effects on FeCl3 -induced venous thrombus formation were 50% (SD 10) for ADTM (p=0·0087 vs vehicle control) and 42% (6) for clopidogrel (p=0·0093 vs vehicle control; p=0·85 vs ADTM). ADTM increased mean coronary blood flow by 36% (SD 15; p=0·0165 for before vs after ADTM administration) and decreased mean arterial pressure (MAP) from 102 mm Hg (2·7) to 96 mm Hg (1·3; p=0·0031). Coronary blood flow did not differ between before and after nitroglycerin administration (p=0·49), but nitroglycerin did decrease mean arterial pressure from 102 mm Hg (1·6) to 92 mm Hg (1·5; p=0·0076). ADTM and nitroglycerin reduced the infarct size of cardiac tissue by a mean of 10% (SD 3; p=0·0217) and 8% (2; p=0·0072), respectively. Interpretation: ADTM is a ligand that targets ERp57 and displays antiplatelet and cardioprotective effects in animal models. ADTM represents a potential lead compound for further investigation and development of new antiplatelet drugs with reduced bleeding risk. Funding: The National Natural Science Foundation of China (NSFC-81403139) and University of Macau (MYRG2015-00161-ICMS-QRCM).